The Influence of Early Lactation Counseling on the Success of Early Breastfeeding Initiation - Ell Fabiola; Dahlia Puspita; Eliyana Eliyana (International Journal of Nursing and Midwifery Research, 2025)
Early Breastfeeding Initiation (IMD) is a critical practice that contributes to neonatal survival, immune protection, mother–infant bonding, and long-term breastfeeding success. Despite strong policy support, the implementation of IMD remains suboptimal in many health care settings. One factor believed to influence IMD success is early lactation counseling provided during pregnancy or early labor. This study aimed to examine the influence of early lactation counseling on the success of Early Breastfeeding Initiation among postpartum mothers. This research employed a quantitative analytic design with a cross-sectional approach. The study population consisted of postpartum mothers who delivered at selected health facilities, with samples selected using a purposive sampling technique. Data were collected using structured questionnaires to assess exposure to early lactation counseling and observation checklists to measure IMD success indicators, including immediate skin-to-skin contact, initiation of breastfeeding within the first hour, and effective infant latch. Data analysis was conducted using the Chi-square test and logistic regression to determine the association and control for potential confounding variables. The results showed that mothers who received early lactation counseling had a significantly higher rate of successful IMD compared to those who did not receive counseling (p < 0.05). Early lactation counseling remained a significant predictor of IMD success after controlling for confounding factors such as mode of delivery, parity, maternal education, and support from health workers or family. In conclusion, early lactation counseling has a significant influence on the success of Early Breastfeeding Initiation. Integrating structured and comprehensive lactation counseling into routine antenatal and intrapartum care is essential to improve IMD implementation and support optimal maternal and neonatal health outcomes.